CrOx supported on high-silica HZSM-5 for propane dehydrogenation - Hu, Zhong-Pan; Wang, Yansu; Yang, Dandan; Yuan, Zhong-Yong (Journal of energy chemistry, 2020)
Industrial propane dehydrogenation (PDH) catalysts generally suffer from low catalytic stability due to the coke formation onto the catalyst surface to cover the active sites. The exploitation of an efficient catalyst with both high catalytic selectivity and long-term stability toward PDH is of great importance but challenging to make. Herein CrOx supported on high-silica HZSM-5 with a SiO2/Al2O3 ratio of 260 (Cr/Z-5(260) is synthesized by a simple wet impregnation method, which exhibits high catalytic activity, good selectivity and excellent stability for PDH. At a weight hourly space velocity (WHSV) of 0.59 h−1, a propylene formation rate of 4.1 mmol gcat−1 h−1 (~ 32.6% propane conversion and ~ 94.2% propylene selectivity) can be maintained over the 5%Cr/Z-5(260) catalyst after 50 h time on stream, which is much better than commercial Cr/Al2O3 (Catofin process, catalyst life is several hours) at the same reaction conditions. With increasing the WHSV to 5.9 h−1, a high propylene formation rate of 27.9 mmol gcat−1 h−1 can be obtained over the 5%Cr/Z-5(260) catalyst after 50 h time on stream, demonstrating a very promising PDH catalyst. Characterization results and Na+ doping experiments reveal that the Cr species combined with Brønsted acid sites in Cr/HZSM-5 catalysts are responsible for the high catalytic performance. In particular, the Brønsted acid sites in HZSM-5 zeolite could increase the propane adsorption and enhance the CH bond activation. Furthermore, the high surface area and well-defined pores of HZSM-5 zeolite can provide a special environment for the dispersion and stabilization of Cr species, thus guaranteeing high catalytic activity and stability. CrOx supported on high-silica HZSM-5 exhibits high catalytic activity, good selectivity and excellent stability for propane dehydrogenation (PDH). [Display omitted]